The ballad of Gregorio Cortez [videorecording (DVD)] - Young, Robert M., 1924-; Young, Robert M., 1924-; Olmos, Edward James; Gammon, James; Bower, Tom, 1938-; Paredes, Américo, 1915-1999 (Criterion collection, 2018)
Set in 1901 Texas, a Mexican-American farmer must run for his life after he is accused of murdering a Texas Ranger.